Purchasing behavior of growing-up milk powder - Chan, Chui Yen (2000)
The milk powder industry has expanded extensively during the last decade and has been constantly being improved. For instance, in the children's milk powder category, age segmentation has been introduced by some milk companies. Thus, an attempt to understand the milk powder purchasing behavior among parents will be beneficial to marketers in order to implement effective marketing strategies. A total of 128 respondents have participated in the research, out of which 115 of their child consumed milk powder. A majority of the respondents were SPM/STPM holders, living in the Klang Valley. The research examines the aspects of brand selection, factors affecting the change of milk powder and evaluates the importance of age segmented milk powders among parents. In addition, the role of advertisement in influencing purchasing decision is also being looked into. Nonetheless, for children who do not consume milk powder, an analysis is carried out to determine the causes. Using the Bivariate Correlation Analysis - Spearman's Rho, brand loyalty among consumers is examined. Results show that there is a high possibly that children aged 3 to 7 will continue using the same brand when the change of milk powder occurs. Another statistical method being employed is the Chi-square Tests. This method presents the results of the relationship between family income and spending on milk powder. Lastly, it is also used to evaluate if there is a relationship between the age of child and brand loyalty. However, findings suggest that there is no significant relationship between the two in both areas of concern.